Isbat Nikah Persperktif Maqosid Syariah - Umar Faruq (Pusat Riset dan Inovasi Nasional, 2023)
Marriage isbat is the validation of a marriage that has been carried out according to Islamic law but has not been registered in court and marriage isbat is carried out in the Religious Court. Meanwhile, in many cases, up to now there are still many people who have not registered their marriages. So, people who do not marry before a religious court must carry out a marriage isbat so that their marriage is recognized by the State. Based on statutory regulations, marriages must also be performed in the Religious Courts, because marriages that are not registered have no legal force. The type of research used in this paper is Library Research. Using primary data sources that use the main material from books from scholars. Secondary material as support for this research uses books, articles, papers that discuss the subject of marriage isbat. Based on research that has been carried out by researchers, it can be concluded that the implementation of marriage isbat is in accordance with the concept of maqasid sharia in safeguarding human benefit, so that marriage isbat is included in the realm of doruriyat maslahat in hifdzu an-nasl (protecting offspring) and hifdzu al-mal (protecting property) because can protect the rights of children and inheritance for children and wives.